The applicability of green productivity tools: An analytical study in a sample of industrial companies in the province of Nineveh - احمد احمد عوني (Journal of Economics and Administrative Sciences, 2013)
The current research aims to identify the most important green productivity tools GPT and the possibility of applied in industrial companies in general and the companies operating in the province of Nineveh, in particular, as well as the study of some personality characteristics and functional, which is believed to be an impact on the application of these tools in industrial companies. Accordingly, the research community of managers in the company of medicines and medical supplies ready-made clothes _ operating in the province of Nineveh, who are (80) while the manager was subjected to research procedures (49) Director representing (61.25%) of the research community. For the purpose of achieving the objective of the study researcher approach the case study in an attempt to investigate the possibility of application of GPT and the compatibility of the data that was obtained from the use of form resolution with the reality of industrial companies of Iraq and the study found a number of conclusions was the most prominent: the lack of possibility to apply some of the GPT in the industrial companies of Iraq due to lack of infrastructure required by the application of GPT its image full and hence the study recommends the need to provide material and moral support of industrial companies of the Iraqi for the implementation of GPT, which will impact on the preservation of the environment on the one hand and improve the productivity levels of the other.